Strategi Menurunkan Pencemaran Air di Sentra Industri Penyamak Kulit di Sukaregang Kabupaten Garut - Fadilah Ghani Azis; Aan Julia (Bandung Conference Series: Economics Studies, 2023)
Abstract. Water pollution is a change in a water reservoir such as rivers, lakes, reservoirs, oceans caused by human activities. This study discusses strategies related to reducing water pollution in the leather tanning industry center Sukaregang Garut. This study aims to determine the condition of water pollution in the Sukaregang tannery industrial center, to determine IFAS and EFAS factors such as the strengths, weaknesses, opportunities and threats of the Sukaregang tannery. and how the results of the SWOT strategy in reducing water pollution. Using a descriptive analysis method with a quantitative approach. The data used in this study are primary data obtained through interviews and secondary data obtained from existing research or information. Based on the results of the study, there are 3 WO strategies, namely increasing the operation of using WWTP as a precondition for marketing a wider market, business actors can set aside revenue from sales to make it easier to pay for WWTP operational costs and business actors create a sales quantity limit system so that waste reduces waste treatment. . There are also 2 WT strategies, namely the government is more assertive in imposing sanctions on business actors who do not have an WWTP and increasing supervision from the government regarding water pollution to the point that money keeps its mouth shut. Abstrak Pencemaran air merupakan terjadinya perubahan di suatu tempat penampungan air seperti sungai, danau, waduk, lautan yang diakibatkan oleh aktivitas manusia. Penelitian ini membahas terkait strategi menurunkan pencemaran air di sentra industri penyamak kulit Sukaregang Garut.Penelitian ini bertujuan untuk mengetahui kondisi pencemaran air di sentra industri penyamak kulit Sukaregang, mengetahui faktor IFAS dan EFAS seperti kekuatan, kelemahan, peluang dan ancaman penyamak kulit Sukaregang. serta bagaimana hasil strategi SWOT dalam menurunkan pencemaran air. Menggunakan metode analisis deskriptif dengan pendekatan kuantitatif. data yang digunakan dalam penelitian ini adalah data primer yang didapat melalui hasil wawancara dan sekunder yang didapat dari penelitian atau indormasi yang sudah ada. Berdasarkan hasil penelitian terdapat 3 strategi WO yaitu meningkatkan operasi penggunaan IPAL sebagai bentuk prasyarat dari pemasaran pasar yang lebih luas, pelaku usaha bisa menyisihkan pendapatan dari penjualan untuk memudahkan dalam membayar biaya operasional IPAL dan pelaku usaha membuat sistem batasan kuantitas penjualan agar limbah untuk mengurangi pengolahan limbah. Juga terdapat 2 strategi WT yaitu pemerintah lebih tegas dalam memberikan sanksi untuk pelaku usaha yang tidak memiliki IPAL dan meningkatkan pengawasan dari pemerintah terkait adanya pencemaran air hingga uang tutup mulut.